2015
DOI: 10.1016/j.ajic.2015.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and phenotypic characterization of methicillin-resistant Staphylococcus aureus isolates causing bacteremia at a major hospital in southern Mississippi

Abstract: Staphylococcus aureus is the predominant cause of bacteremia worldwide. We assessed the molecular epidemiology and antibiotic resistance of MRSA isolates causing bacteremia in Southern Mississippi. Diverse genetic backgrounds in terms of SCCmec, PFGE, and MLST types of MRSA were identified as causing bacteremia in Mississippi. A strong association of Panton – Valentine Leukocidin (PVL) genes with elevated vancomycin MIC is one of the important findings of our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similarly, a 15-year study in Taiwan concluded that CA-MRSA strains have replaced HA-MRSA in neonatal units [5]. Also, a predominance of CA-MRSA in the skin and soft tissue infections (SSTIs) and bacteremia isolates has been reported in Australia, China, the USA, and North Africa among other regions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a 15-year study in Taiwan concluded that CA-MRSA strains have replaced HA-MRSA in neonatal units [5]. Also, a predominance of CA-MRSA in the skin and soft tissue infections (SSTIs) and bacteremia isolates has been reported in Australia, China, the USA, and North Africa among other regions [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus aureus (S. aureus) is a common pathogen and can cause different kinds of infection in both hospitals and communities (Knox et al, 2015;Samanta et al, 2015). Several parts of human body can carry S. aureus and the nasal cavity is the main part.…”
Section: Introductionmentioning
confidence: 99%